Retrorectal (Pre Sacral) Dermoid Cyst: a case report - Atiyeh Mansouri; Nasrin Kamali; Masoumeh Javdan Mehr; Mostafa Sadeghi (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2019)
Introduction: Retrorectal tumors are relatively rare. Dermoid cysts are of the family of retrorectal tumors which are usually benign and found in young women. In this study, a case of retrorectal dermoid cyst is reported. Case presentation: The patient was a 25-year-old woman who had referred to Mashhad Mehr hospital with symptoms of nausea, vomiting, flatulence and change in bowel movements and pelvic pain. The physical examinations by laparoscopy revealed a mass measuring 74×62 in posterior uterus. The patient underwent surgery and the cyst was completely excised. The patient discharged after five days and no postoperative complications were reported in the follow up. Pathological results reported dermoid cyst. Conclusion: Surgery is the main treatment of retrorectal lesions and tumors. The use of imaging results such as MRI and CT-scan is recommended for more precise diagnosis of the nature and location of the lesion and to select the best surgery approach appropriate to the location of the mass.